How to find fulfilling work - Krznaric, Roman, ....- (London : Macmillan, 2012)
The desire for fulfilling work is one of the great aspirations of our age and this inspirational book reveals how one might make it a reality. It explores the competing claims we face for money and status while doing something meaningful and in tune with our talents. Drawing on wisdom about work that is to be found in sociology, psychology, history and philosophy, Roman Krznaric sets out a practical and innovative guide to negotiating the labyrinth of choices, overcoming the fear of change, and finding a career that makes you thrive.
Keywords: Loopbaanplanning